HYDRODYNAMIC DESCRIPTION OF THE ELECTRON MOTION IN THE GRAPHEN CRYSTAL LATTICE - B. V. Alexeev; I. V. Ovchinnikova (Тонкие химические технологии)
The motion of the charged particles in graphen in the frame of the quantum non-local hydrodynamic description is considered. It is shown as results of the mathematical modeling that the mentioned motion is realizing in the soliton forms. The dependence of the size and structure of solitons on the different physical parameters is investigated.